The Influence Of Education And Competence Onemployee Performance At PT. Esaputlii Prakarsa Utama Barru South Sulawesi - Ilham Ilham; Andi Ridwan Makkulawu (Citakonsultindo, 2023)
There are two purposes for writing the final assignment, namely (1) to determine the effect of employee education on employee performance at PT. Esaputlii Prakarsa Utama, (2) Knowing the influence of employee competence on employee performance at PT. Esaputlii Main Initiative. This research was conducted to employees of PT. Esaputlii Main Initiative, Barru. The number of samples in this study was 40. The data sources used in this final project were primary data and secondary data while the data collection methods used were observation, questionnaires and literature study. The sampling technique used by the author is purposive sampling. This final project uses multiple linear regression data analysis while to determine the effect of variables X 1 and X 2 on variable Y using the t (partial) test. The results of data analysis show that employee education has a significant effect on employee performance at PT. Esaputlii Prakarsa Utama, this is because based on a comparison of the t count and t table it turns out that t count is greater than t table with the acquisition value (2.386 > 2.02619), competence has a significant effect on employee performance at PT. Esaputlii Prakarsa Utama, this is because based on a comparison of the t count and t table it turns out that t count is greater than t table with the acquisition value of ( 7.038 > 2.02619).